2012
DOI: 10.1016/j.neuroimage.2011.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Network modulation during complex syntactic processing

Abstract: Complex sentence processing is supported by a left-lateralized neural network including inferior frontal cortex and posterior superior temporal cortex. This study investigates the pattern of connectivity and information flow within this network. We used fMRI BOLD data derived from 12 healthy participants reported in an earlier study (Thompson, C. K., Den Ouden, D. B., Bonakdarpour, B., Garibaldi, K., & Parrish, T. B. (2010b). Neural plasticity and treatment-induced recovery of sentence processing in agrammatis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
53
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 54 publications
15
53
1
2
Order By: Relevance
“…A recent DCM study with a picture-sentence matching task has suggested that L. F3op/F3t received driving inputs [44], which was consistent with our DCM results. Moreover, our previous studies revealed that the functional connectivity between L. F3t/F3O (pars orbitalis) and L. AG/SMG was selectively enhanced during sentence processing [45], and that L. AG/SMG was also activated during the identification of correct past-tense forms of verbs, probably reflecting an integration of syntactic and vocabulary knowledge [46].…”
Section: Discussionsupporting
confidence: 92%
“…A recent DCM study with a picture-sentence matching task has suggested that L. F3op/F3t received driving inputs [44], which was consistent with our DCM results. Moreover, our previous studies revealed that the functional connectivity between L. F3t/F3O (pars orbitalis) and L. AG/SMG was selectively enhanced during sentence processing [45], and that L. AG/SMG was also activated during the identification of correct past-tense forms of verbs, probably reflecting an integration of syntactic and vocabulary knowledge [46].…”
Section: Discussionsupporting
confidence: 92%
“…The inferior parietal lobule and the inferior frontal gyrus, two areas known to be interconnected by components of the arcuate fasciculus (Catani & Mesulam, 2008), are major components of the dorsal route, which mediates phoneme-to-grapheme conversion. This route is also critically important for the phonological loop (Amici, et al, 2007) and morphosyntax (den Ouden, et al, 2012; Wilson, et al, 2011), explaining why nonword spelling, the one type of spelling that most heavily relies on the phonological route, was significantly correlated with task of repetition and grammaticality. The correlation of phonological agraphia with atrophy in the inferior parietal lobule and the inferior frontal gyrus is also consistent with the known prominence of agraphia in Broca's aphasia and the Gerstmann syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Sentence comprehension in cognitively healthy individuals also is supported by a left-lateralized network that includes the inferior and middle frontal gyri, the middle and superior temporal gyri, and the angular gyrus (see den Ouden et al, 2012; Friederici, 2011; Indefrey, Hellwig, Herzog, Seitz, & Hagoort, 2004; Segaert, Menenti, Weber, Petersson, & Hagoort, 2012; Thompson & Kielar, in press; Thompson, den Ouden, Bonakdarpour, Garibaldi, & Parrish, 2010, and many others). Less is known about the neural basis of grammatical production in cognitively healthy speakers, but again neuroimaging studies have highlighted the left fronto-temporal-parietal language network for sentence production, in particular inferior frontal regions (Grande et al, 2012; Indefrey, Hellwig, Herzog, Seitz, & Hagoort, 2004; Segaert, Menenti, Weber, Petersson, & Hagoort, 2012).…”
Section: Neural Mechanisms Of Grammatical Processing Deficitsmentioning
confidence: 99%